Models of freight transport system development - Baublys, Adolfas; Smičius, Algimantas (Transport, 2002)
The article analyses the following issues: I) Basicfactors determining Transport system development;2) Transport system services and their assessment; 3) Goods handling Transport system as a research object. The objective of goods handling Transport system development and improvement is to estabhsh a general goods handlmg Transport system of the country ensuring satisfaction of national needs for high quality Transport service in this field; 4) Models of Transport modes interaction; 5) Determinate models for main Transport network development; 6) Model of development of private freight road Transport. First Published Online: 19 Dec 2011